Latihan Fisik Terarah Penderita Post Sindrom Koroner Akut dalam Memperbaiki Otot Jantung - Fatin Lailatul Badriyah (Universitas Muhammadiyah Yogyakarta, 2014)
Background: One of cardiovascular disease and very scary is acute coronary syndrome (ACS). It is currently one of the leading causes of death in developed and developing countries, including Indonesia. SKA can be either acute myocardial infarction, including ST-segment elevation MI (STEMI) and non- segment elevation MI (NSTEMI), and unstable angina. Globally become the fi rst cause of death in developing countries, replace mortality due to infection. Systematic eff ort is needed and intensively to prevent the increasing cases of illness, among others with cardiac rehabilitation. One of cardiac rehabilitation can be done is directed physical exercise. Objectives: To determine the eff ect of derected physical exercise on the function of cardiac muscle, assessed based on the results of blood pressure, pulse and ECG. Methods: The study uses a quasi-experiment design, the research subjects totaling 64 people divided into intervention group as 32 peoples and control group of 32 peoples, carried out in hospital cardiac clinic Siti Khodijah Surabaya. Results: Wilcoxon test and Mann Whitney test, obtained results there is a significant influence on tension with p-value of 0.001 (p 0.05), there is no signifi cant eff ect on the change of the pulse with the p-value of 1.000 (p 0.05), and signifi cantly infl uence changes in EKG with P-value 0.000 (P 0.05). The results of the Nagelkerke test and Chi-square, obtained results physical exercise directed has contributed to the tension of 16.4%, OR = 9.552, while the ECG changes of 47.0%, OR = 27.617. Conclusions: Physical exercise directed has a signifi cant eff ect on blood pressure and EKG, where the directional physical exercise has a more signifi cant eff ect on blood pressure than the ECG. Key word: Physical exercise directed and Coronary acute syndrome (ACS)